FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2015 - Gresella Junita Samosir, 13.05.52.0177; Maryono, Maryono (Students' Journal of Accounting and Banking, 2017)
This study aims to determining the effect of fixed tangible asset, Profitability, Growth and likuidity on capital structure at manufacture company listed in Indonesian Stock Exchange 2012-2015. A kind of data used in this research is of secondary data, this data obtained from financial statement in IDX Data analysis technique used is multiple linear regression analysis. The method used is purposive sampling with set four years is 2012-2015 The results of this study show that fixed tangible assets and Likuidity significant positive correlation to capital structure. Profitability and Growth significantly negative to the capital structure.Keywords: Fixed Tangible Asset, Profitability, Growth, Likuidity and Capital Structure